1983
DOI: 10.1111/j.1476-5381.1983.tb10535.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the stereoselectivity of the P2‐purinoceptor

Abstract: 1ATP, 2-chloro-ATP, 2-methylthio-ATP, and their unnatural L-enantiomers, were synthesized and their effects tested on the guinea-pig taenia coli and urinary bladder, and the stimulated frog ventricle. 2 The potent P2-purinoceptor agonists, 2-chloro-ATP and 2-methylthio-ATP were, respectively, 30 and 200 times more effective than ATP in relaxing the guinea-pig taenia, but approximately as effective as ATP in contracting the guinea-pig bladder and augmenting the force of contraction of the frog ventricle. 3 A hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1

Year Published

1985
1985
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 23 publications
1
46
1
Order By: Relevance
“…2-MeSATP has been known for a long time to be a potent P2y-purinoceptor agonist (Gough et al, 1973;Satchell & Maguire, 1975;Burnstock et al, 1983) although it can also activate P2x-purinoceptors at a higher concentration (Howson et al, 1988;Theobald, 1992). Further modifications on the C-2 position produced 2-HeSATP, 2-CyaHeSATP, 2-phenylethylthio ATP, and 2-(2-p-nitrophenylethyl)thio ATP, which did not show significantly increased efficacy on P2Y-purinoceptors, while the potency on P2x-purinoceptors have been greatly enhanced (Fischer et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…2-MeSATP has been known for a long time to be a potent P2y-purinoceptor agonist (Gough et al, 1973;Satchell & Maguire, 1975;Burnstock et al, 1983) although it can also activate P2x-purinoceptors at a higher concentration (Howson et al, 1988;Theobald, 1992). Further modifications on the C-2 position produced 2-HeSATP, 2-CyaHeSATP, 2-phenylethylthio ATP, and 2-(2-p-nitrophenylethyl)thio ATP, which did not show significantly increased efficacy on P2Y-purinoceptors, while the potency on P2x-purinoceptors have been greatly enhanced (Fischer et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…A rank potency order of a,fi-methylene, 0,ymethylene ATP > ATP = 2-methylthio ATP is indicated in these tissues. In the guinea-pig taenia coli (Satchell & Maguire, 1975;Maguire & Satchell, 1979;Burnstock et al, 1983), the rabbit portal vein (Kennedy & Burnstock, 1985b), the pig and rat aorta (Martin et al, 1985a;White et al, 1985) and the rat femoral artery , P2-purinoceptors mediate relaxations. A rank order of potency in these tissues is 2-methylthio ATP > ATP > a,,-methylene ATP, ,y-methylene ATP.…”
Section: Pharmacologymentioning
confidence: 99%
“…Similar studies of purine nucleotide potencies have been carried out in a number of other tissues and a comparative agonist potency order has been demonstrated (see . In the guinea-pig vas deferens (Fedan et al, 1982;Burnstock et al, 1983;, the rat and guinea-pig urinary bladder (Brown et al, 1979;Burnstock et al, 1983), the perfused pancreas vascular bed (Chapal & Loubatieres-Mariani, 1983), the rat aorta and femoral artery White et al, 1985) and the rabbit ear artery (Kennedy & Burnstock, 1985a), P2-purinoceptors mediate contraction. A rank potency order of a,fi-methylene, 0,ymethylene ATP > ATP = 2-methylthio ATP is indicated in these tissues.…”
Section: Pharmacologymentioning
confidence: 99%
“…Thus the receptor has entirely distinct properties from the ectonucleotidases and probably recognises nucleotide uncomplexed to a metal cation. The magnitude of purinoceptor-induced responses may well be affected, however, by the rate of catabolism exerted by neighbouring ectonucleotidases [19,20] ; thus studies of the type reported here are also important for the rational design of agents that selectively interact with ectonucleotidases or purinoceptors.…”
Section: Discussionmentioning
confidence: 99%